(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Ginger is a household spice used globally for different purposes. As per Ayurveda, it is considered to possess therapeutic properties for various ailments. Although ginger has Pramehagna (anti-diabetic) property, there are very few formulations for diabetes that contain this as an ingredient. However, some pharmaceutical and clinical studies have shown significant anti-diabetic property of ginger. According to Ayurveda, Ardraka (fresh rhizome) and Shunti (dry rhizome) have different properties and are widely used in many formulations. To analyze the difference between both forms of ginger in varied forms, phytochemical screening, and HPTLC study was done on Ardraka swarasa (juice of fresh rhizome), Shunti churna (powder), Ardraka and Shunti Kashaya (decoction of fresh and dry ginger), Ardraka and Shunti Hima (cold infusion of fresh and dry ginger), Ardraka and Shunti phanta (cold decoction of fresh and dry ginger). Alkaloids were present abundantly in Ardraka swarasa, Ardraka kashaya, Shunti kashaya, Shunti hima and Shunti phanta. Flavonoids were present in excess only in Ardraka swarasa. HPTLC analysis showed more peaks in Kashaya of both forms of rhizomes and Ardraka phanta.